TYPOGRAPHIC IMAGE AS A VISUAL COMMUNICATION INSTRUMENT - KURAN, Onur; UÇAR, Fikret (SSD Journal, 2022)
Writing is one of the main communication tools that has been widely used since the Sumerian civilization discovered it. While it had a symbolic attitude in its form in the first periods of its discovery, it was simplified over time and brought to the basic form we use today. With the discipline of typography, which allows us to use writing, which is one of the main constituent of visual communication and graphic design, both aesthetically and functionally, graphic designers visualize writing in variety of different forms, traditional and contemporary. Today, visual communication is one of the most important concepts encountered in every aspect of human life. People are now trying to meet their communication needs faster by looking and seeing instead of reading. In this study, rather than recording the verbal language, which is the main function of writing, it is explained by giving examples how writing is used as an imaginary language of expression in different art and design disciplines, especially in the graphic design discipline. In this direction, the typographic image style is defined in the study and the concept of typographic image is explained by giving examples in the disciplines of sculpture, architecture, interior architecture, textile and fashion design, and industrial design, especially in the discipline of graphic design.